2020
DOI: 10.3390/molecules25071564
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids and Ohmic Heating in Combination for Pd-Catalyzed Cross-Coupling Reactions: Sustainable Synthesis of Flavonoids

Abstract: In order to meet the increasing demand for environmentally benign chemical processes, we developed a Suzuki–Miyaura reaction protocol based on the combination of ohmic heating (ΩH) and supported ionic liquid phase catalysis (SILPC) in aqueous media. This methodology was applied to the synthesis of a series of flavonoid derivatives, including isoflavones, styrylisoflavones, and diarylalkenylisoflavones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There are numerous documented organic reactions carried out under ohmic heating (Soengas et al, 2016). Recently, Silva et al (Silva et al, 2020) have reported a Suzuki-Miyaura reaction protocol that is based on the combined use of ohmic heating (ΩH) and supported ionic liquid phase catalysts. This methodology was applied to obtain different flavonoid derivatives in aqueous media in a sustainable and efficient way.…”
Section: Ohmic and Induction Heatingmentioning
confidence: 99%
“…There are numerous documented organic reactions carried out under ohmic heating (Soengas et al, 2016). Recently, Silva et al (Silva et al, 2020) have reported a Suzuki-Miyaura reaction protocol that is based on the combined use of ohmic heating (ΩH) and supported ionic liquid phase catalysts. This methodology was applied to obtain different flavonoid derivatives in aqueous media in a sustainable and efficient way.…”
Section: Ohmic and Induction Heatingmentioning
confidence: 99%
“…Silva and co-corkers have recently developed an environmentally benign, economically friendly, and sustainable Suzuki–Miyaura reaction of halo and dihalo dienyl derivatives and boronic acids employing Pd(II) immobilized in a silica-supported ionic liquid in water using ohmic heating (ΩH) [ 74 ]. Ohmic heating is and advanced thermal technology recently developed for organic synthesis [ 75 , 76 ] which leads activation on several reactions, including transition-metal catalysed cross-couplings [ 77 ].…”
Section: Transition Metal-catalysed Cross-coupling Reactionsmentioning
confidence: 99%
“…These disadvantages can be avoided with modern technologies such as ohmic heating [ 11 ]. The latter is a thermal treatment that heats food by passing an alternating electric current through it; as a consequence, this method has a large capacity for rapid and homogeneous heating [ 12 ]. In addition, this technique provides safe and high-quality food products [ 13 ] while preserving their nutritional value [ 10 ].…”
Section: Introductionmentioning
confidence: 99%